The global burden, trends and cross-region inequities of non-communicable diseases attributed to ambient particulate matter pollution - Wang, Songsong; Lai, Hanpeng (Frontiers in Public Health, 2025)
BackgroundAmbient particulate matter poses long-term and geographically uneven health risks, warranting assessment of global burden and regional disparities.MethodsGBD 2019 data was used to assess age standardized rates of mortality (ASMR) and DALY (ASDR) from five chronic diseases due to ambient particulate matter from 1990 to 2019, focusing on temporal trends and cross-regional disparities using the Socio-demographic Index (SDI).ResultsIn 2019, ischemic heart disease (IHD) and stroke accounted for the greatest burdens attributable to ambient particulate matter, with global ASMRs of 30 and 26 per 100,000, respectively, followed by chronic obstructive pulmonary disease (COPD) at 16, tracheal bronchus and lung (TBL) cancer at 6.8, and diabetes mellitus at 4.5. From 1990 to 2019, COPD showed a marked decline with an AAPC on ASMR of −0.47, while diabetes and TBL cancer rose sharply, with AAPCs of 1.57 and 0.75, respectively. ASDR for the five disease had similar patterns. Southeast Asia, East Asia, and Oceania carried the heaviest TBL cancer and stroke burden from 2000 on, North Africa and the Middle East ranked consistently highest for IHD and diabetes mellitus, and South Asia emerged as the global hotspot for COPD after 2005. TBL cancer was concentrated in higher-SDI regions, whereas COPD and diabetes mellitus rose disproportionately in lower-SDI areas. Population growth and aging were the primary drivers of increases across all diseases. Health inequality analysis further showed a general shift of burdens from high- to low-SDI countries, with indices declining from high positive values to lower or even negative values between 1990 and 2019.ConclusionAmbient particulate matter continues to drive unequal disease burdens, especially in low- and middle-SDI regions, and more targeted efforts are thus needed.